Examining the Impact of Technology Overload at the Workplace: A Systematic Review. (July 2022) - Rasool, Tayyba; Warraich, Nosheen Fatima; Sajid, Muhammad
Information and communication technologies have changed and created a ubiquitous work environment for employees to work at any place and at any time. But it also caused technology overload for them. This study aims to evaluate the previously published literature to examine the effects of technology overload in the workplace. This systematic literature review employed a qualitative research design and reviewed articles on technology overload from the workplace perspective. N-Vivo, a qualitative software, was used to create and analyze codes and themes. This study looked at factors that create technology overload such as interruption overload, work-life conflict/work-family conflict, stress, social network service addiction/email addiction, social overload, and lost productivity. This study also established the challenges that knowledge workers/employees have to face at the workplace. Results indicate that self-efficacy, training, and time management are the key strategies to overcome technology overload. This study would contribute to the literature by examining the technology overload in the workplace. It will increase the employees' awareness of strategies to overcome technology overload. It reviewed only empirical studies published about technology overload from the employees' perspective. Future research may be conducted focusing on the employers' perspective regarding technology overload. It has implications for the administration of the workplace to conduct training for the employees before the implementation of new technology. Organizations should establish laws for timings after work hours and disconnection from the internet at home to reduce technology overload.